The impact of macroeconomic variables on FTSE Bursa Malaysia Emas Shariah Index / Siti Nurulhuda Ibrahim … [et al.] - Ibrahim, Siti Nurulhuda; Abdul Hamid, Zuraini; Mohd Nor, Amirudin; Abd Razak, Noraznira (2017)
This research will focus on the relationship between selected macroeconomic variables and Islamic stock market in Malaysia. The objective of this research is to examine the impact of Aggregate Money Supply (M3), Kuala Lumpur Interbank Offer Rate (KLIBOR), Exchange Rate of Malaysian Ringgit-United States Dollar (EXRATE), Industrial Production Index (IPI), Consumer Price Index (CPI), Gold Price (GOLD) and Crude Oil Price (COP), which is combination of monetary, production and commodity toward FTSE Bursa Malaysia Emas Shariah Index (FBMES). In order to achieve the objective, this study applies the Ordinary Least Square using heteroskedasticity robust variance-covariance estimator (VCE robust) and used monthly data over the period of April 2007 - April 2016 from authorized sources which is DataStream (Thompson Reuters). The study revealed that there is a significant relationship between FTSE Bursa Malaysia Emas Shariah Index and the selected variables, namely EXRATE, IPI, CPI, GOLD and COP. However, FTSE Bursa Malaysia Emas Index is found negative, and not significantly affected by KLIBOR. Besides that, we need to exclude M3 due to high correlation with the CPI. This study is important for those market participants, especially for investors and fund manager who need to understand the behavior of the stock market in order to make a right decision in making an investment.